2017
DOI: 10.1186/s12889-017-4863-x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in health among Swedish adolescents - adding the subjective perspective

Abstract: BackgroundSocioeconomic inequalities in adolescent health predict future inequalities in adult health. Subjective measures of socioeconomic status (SES) may contribute with an increased understanding of these inequalities. The aim of this study was to investigate socioeconomic health inequalities using both a subjective and an objective measure of SES among Swedish adolescents.MethodCross-sectional HBSC-data from 2002 to 2014 was used with a total sample of 23,088 adolescents aged 11–15 years. Three measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 40 publications
9
35
1
1
Order By: Relevance
“…With respect to health, SSS showed a significant effect even when controlling for the effect of IOSEP and health, congruent with previous research [21,22]. However, our results differ from other studies [24,25] in which SSS is reported to have a higher impact on health than objective indicators. Moreover, when comparing the models of objective and subjective SEP indicators (both individually and combined), our results show SSS to mediate the relationships between objective SEP and health.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…With respect to health, SSS showed a significant effect even when controlling for the effect of IOSEP and health, congruent with previous research [21,22]. However, our results differ from other studies [24,25] in which SSS is reported to have a higher impact on health than objective indicators. Moreover, when comparing the models of objective and subjective SEP indicators (both individually and combined), our results show SSS to mediate the relationships between objective SEP and health.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, previous findings have reported certain consequences on adolescent health of perceiving oneself as having a low SEP in comparison to others, even after controlling the effect of objective indicators [21,22,23]. Moreover, a study conducted by Ahlborg et al [24] demonstrated that controlling either the objective or subjective factors might affect the others impact on health. For example, the effect of FAS on multiple health complaints diminished or even reverted when SSS was controlled.…”
Section: Introductionmentioning
confidence: 99%
“…This three-category framework was designed as a proxy for young people’s perceptions of their family’s socioeconomic circumstances and implicates a subjective socioeconomic status. It is used frequently in similar studies and has previously been shown to reliably predict health inequalities [16,28,29,30]. It seems that subjective measures of socioeconomic status combine absolute and relative deprivation of current and past social circumstances along with future prospects [31,32].…”
Section: Methodsmentioning
confidence: 99%
“…(3) Socioeconomic indicators include social and economic circumstances, level of education, occupation, gender, family income (affluence), and family sizeboth objective and subjective measurements. (4) While several studies have justified the associations between socioeconomic status (SES) and health across the life course, health inequalities are not consistent through different age groups. (5) Some previous studies support the relative lack of social inequalities (that is a certain level of equalization) in adolescents' health (e.g.…”
Section: Introductionmentioning
confidence: 99%